2015
DOI: 10.1016/j.clinthera.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Remote Monitoring System for Diabetes Control

Abstract: Purpose The use of technology to implement cost-effective health care management on a large scale may be an alternative for diabetes management but needs to be evaluated in controlled trials. This study assessed the utility and cost-effectiveness of an automated Diabetes Remote Monitoring and Management System (DRMS) in glycemic control versus usual care. Methods In this randomized, controlled study, patients with uncontrolled diabetes on insulin were randomized to use of the DRMS or usual care. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 19 publications
1
59
0
4
Order By: Relevance
“…Figure 2 illustrates the quality of the included studies. Most studies received a low risk score for their random sequence generation 54,[56][57][58][59][60][61]63,66 ; however, only 1 study reported method of allocation concealment. 57 While blinding of participants, personnel, and the outcome assessment was reported in only 3 of the 13 studies, 57,61,65 we deemed all studies to be at low risk for performance and detection bias, since the outcome, glycemic control, and its measurement are not likely to be influenced by lack of blinding.…”
Section: Methodological Quality Assessment Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 illustrates the quality of the included studies. Most studies received a low risk score for their random sequence generation 54,[56][57][58][59][60][61]63,66 ; however, only 1 study reported method of allocation concealment. 57 While blinding of participants, personnel, and the outcome assessment was reported in only 3 of the 13 studies, 57,61,65 we deemed all studies to be at low risk for performance and detection bias, since the outcome, glycemic control, and its measurement are not likely to be influenced by lack of blinding.…”
Section: Methodological Quality Assessment Of Studiesmentioning
confidence: 99%
“…[57][58][59]66 Regarding "other bias," the majority of studies were rated as high risk of bias, as the control groups received usual care only. 54,[58][59][60][61][62]65,66 Those employing an attention control group achieved this by providing usual care plus in-person individual DSME using printed materials, 55,57,63 multiple-choice quizzes, 56 or a mix of in-person group and individual DSME. 64 Of the 13 studies, only 1 received an overall score of low risk of bias.…”
Section: Methodological Quality Assessment Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This month we feature a research report from Katalenich et al, 12 "Evaluation of a Remote Monitoring System for Diabetes Control." The authors evaluated a system that employs text messaging or phone calls to remind patients to test blood glucose levels and that reports results using an automated system.…”
mentioning
confidence: 96%